Keterampilan mengajar guru di Lembaga Pendidikan Al-Ma’arif Kuningan - riza zahrah (Abdimas Siliwangi, 2023)
Al-Ma'arif educational institution stands as many as three educational institutions, namely PAUD Al- Ma'arif, TPA / TKA Al-Ma'arif and DTA Al-Ma'arif. Al-Ma'arif Educational Institution encounters obstacles including aspects of human resources who have educational qualifications that are not in accordance with the field of science or education. Then motivation, innovation and creativity are still low which has implications for the process of organizing ongoing education and teaching. Improving HR aspects in improving HR teaching skills in the learning process in the classroom. Activities to improve HR teaching skills that will have implications for HR innovation and creativity after the development of lesson plan preparation activities and audio-visual media. The output targets to be achieved include: Teaching skills of educators, creativity and innovation of educators in the learning process to improve student learning outcomes and the creation of a pleasant learning atmosphere. The implementation method used in this PKM activity includes the method of technology transfer and continuous assistance.